Leadership Character of the Director General of Immigration: a Hope - Junaidul Fitriyono (Jurnal Administrasi dan Kebijakan Publik, 2023)
The open selection for the position of Director General of Immigration at the Ministry of Law and Human Rights has become a historic moment with the opportunity for non-civil servants to be involved as candidates. This phenomenon illustrates that the public has high hopes for the Director General of Immigration who will be elected. The hope is that Indonesian Immigration will be more advanced and ready to face challenges. This is descriptive research using a literature study that uses various data and information related to Immigration issues, the selection of the Director General of Immigration and the challenges of Immigration in the future. The Director General of Immigration must be able to be an example (example), have sufficient experience (experience), educated (education), understand the environment and organizational values (environment) and be able to evaluate the program well (evaluation). Therefore, it is important to remind that the Director General of Immigration must understand the work culture of the organization, the ability to change for the better, the ability to make effective decisions, the ability to lead and communicate, the drive to be able to collaborate with strategic partners, equal opportunities in order to develop capacity, be able to achieve performance targets, maximize assets and potential, manage the quality of public services that are getting better and the ability to bring this organization to a better direction.